Every year, every christmas, this is christmas - Vandross, Luther; Sony Music Entertainment (New York : Sony Music Entertainment, 1995)
Contains two christmas songs.
Every Year, Every Christmas (5:06) -- This Is Christmas (4:45).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Christmas music